Eficiencia de producción en sorgo de grano (sorghum vulgare pers) - Grand-Pierre, C (International Center for Tropical Agriculture, 1972)
Various morphological factors affecting the efficiency of production in sorghum (Sorghum vulgare Pers.) were studied at the beginning and the end of the grain filling period. The first part included the morphological description of the plant at the time of anthesis, considering the following parameters: number of leaves, height of the plant, length of the panicle, leaf area of the five uppermost leaves, total leaf area, dry weight of leaves, and stem and panicle dry weights. The second part of the study involved the following measurements at final harvest: dry weight of the 5 upper leaves, dry weight of the lower leaves, dry weight of stem and panicle, total dry weight of the plant, dry weight of grain from 5 random plants, grain weight of plants with 5 upper leaves only and grain weight of plants without its 5 upper leaves, and yield per hectare. It was found that the 5 upper leaves contributed 89% of total plant yield. There was a highly significant correlation between total dry weight and total leaf area of the plant, with a correlation coefficient of r = 0.9884. In addition, the leaf of greatest dry weight and greatest leaf area was either the second leaf of the third leaf from the top. The dry weight of the leaves at the moment of anthesis was statistically equal to the dry weight of the leaves at final harvest.